In vitro antiviral activity of lactobacillus casei and bifidobacterium adolescentis against rotavirus infection monitored by NSP 4 protein production (2016)
Aims The aim of this study was to determine the antiviral activity of four probiotic metabolites (Lactobacillus and Bifidobacetrium species) against rotavirus in vitro infection monitored by the NSP 4 protein production and Ca2+ release. Methods and Results The antiviral effect of the metabolites was performed due a comparison between a blocking model and an intracelullar model on MA 104 cells, with the response of NSP 4 production and Ca2+ liberation measured by flow cytometry. Significant results were obtained with the metabolites of Lactobacillus casei, and Bifidobacterium adolescentis in the reduction of the protein production (P = 0·04 and P = 0·014) and Ca2+ liberation (P = 0·094 and P = 0·020) in the intracellular model, which suggests a successful antiviral activity against RV infection. Conclusions This study demonstrates that probiotic metabolites were able to interfere with the final amount of intracellular NSP 4 protein and a successful Ca2+ regulation, which suggests a new approach to the mechanism exerted by probiotics against the rotavirus infection. Significance and Impact of the Study A novel anti‐rotaviral effect exerted by probiotic metabolites monitored by the NSP 4 protein during the RV in vitro infection and the effect on the Ca2+ release is reported; suggesting a reduction on the impact of the infection by decreasing the damage of the cells preventing the electrolyte loss.